The Function of Prosodic Features in Conferences in Spanish and in English - Giménez, Florencia (2026)
This article offers a comparative prosodic analysis of two conferences, one in English and one in Spanish, around similar topics and delivered by the same lecturer, a native speaker of Spanish who is also a speaker of English as a foreign language (FL). The prosodic analysis offered in this article is based on the model of Discourse Intonation (Brazil, 1997; Brazil et al., 1980) in relation to three functions of intonation: discourse, focusing, and interpersonal. The analysis aims to compare the two conferences and to explore how the lecturer resorts to the different prosodic features to organize (discourse function) and structure discourse (focusing function), and to relate to the audience through the message (interpersonal function) in each conference. In line with previous research, the prosodic analysis reveals similarities and differences between the conferences analysed. A finding worth pointing out is the fact that, in the conference in English, there are instances in which the L1 of the speaker seems to exert some influence at the level of prominence. In those cases, it is questionable whether prominence contributes to the focusing function of intonation.